By M. "HARD" AND "SOFT" LINES IN ECONOMIC DEVELOPMENT - Bronsenbrenner, M. (Dirasat in Economics and Business, 1966)
It is flattering to be asked for an essay relevant to the economic problems of North Africa, when one has never visited that area and knows almost nothing about its languages, history, and cultures. If the ideas or “insights” which follow do not fit North African realities, let the reader remember their derivation — partly from the international Ivory Tower, and partly from conditions in developing and reconstructing countries on the Asian side of the Pacific Ocean.